Sport Psychology : The Basics - Tod, David; Thatcher, Joanne; Rahman, Rachel; Series Editors: Holt, Nigel; Lewis, Rob (New York Palgrave Macmillan, 2010)
In this student-friendly introduction, the authors consider the psychological effects of sport on both the individual and the group. Topics covered include motivation, performance, mental health and leadership, offering a balanced and in-depth resource for students interested in learning more about sport psychology.
Include Tables, Figures, Glossary, References and Index.
Keywords: Sports -- Psychological aspects of Sports -- Sports - Psychological aspects